PHYTOCHEMICAL TEST AND STABILITY TEST OF PIGMENT OF KETAPANG LEAF (Terminalia catappa Linn.) - Sulistiyawati, Rizki Ramadhani; Saleh, Chairul; Kartika, Rudi (Jurusan Kimia FMIPA UNMUL, 2021)
Extraction of ketapang leaf (Terminalia catappa Linn) was carried out by maceration method using 96% ethanol. Phytochemical test results showed that the ketapang leaf extract contained tannin compounds. Stability test of ketapang leaf extract was carried out on the influence of temperature 40, 60 and 800C, the effect of pH (3, 4 and 5) and the effect of storage duration 1, 3 and 5 days using wavelength UV. The results of this study indicate that the ketapang leaf dye is stable at pH 3-4, stable decrease by heating at temperature 40-800C and stable at storage for 1-3 days.